(untitled) (Historia, 2021)
This remarkable account of the colonisation of the Western Cape begins with an evocative sense of place: the source of the Olifants River in the Cedarberg Mountains. The river is the geographical, social and political frontier in relation to which Mitchell constructs her account of the colonisation of the early eighteenth century.